2022
DOI: 10.1038/s41467-022-32852-6
|View full text |Cite|
|
Sign up to set email alerts
|

Smart low interfacial toughness coatings for on-demand de-icing without melting

Abstract: Ice accretion causes problems in vital industries and has been addressed over the past decades with either passive or active de-icing systems. This work presents a smart, hybrid (passive and active) de-icing system through the combination of a low interfacial toughness coating, printed circuit board heaters, and an ice-detecting microwave sensor. The coating’s interfacial toughness with ice is found to be temperature dependent and can be modulated using the embedded heaters. Accordingly, de-icing is realized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 68 publications
(89 reference statements)
1
25
0
Order By: Relevance
“…where E Ã is the effective modulus of the interface. As shown previously by the authors 9,10 and others, 11…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…where E Ã is the effective modulus of the interface. As shown previously by the authors 9,10 and others, 11…”
Section: Introductionsupporting
confidence: 76%
“…Recent work has reported that Γ is temperature dependent, at least for UHMWPE. 10 As shown in Fig. 4a, no significant difference was found for Γ measured at −5, −10, and 20 °C for the ceramic erosion-resistant materials.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Deicing methods that rely on human intervention could be inefficient and outdated . Consequently, researchers have been exploring new passive anti-icing/deicing solutions predicated on the intrinsic properties of materials. , However, achieving both passive anti-icing/deicing functions on the same surface remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Microwave structures have been investigated in various geometries, such as planar antennas and resonators mounted on substrates, flexible resonant surfaces, and waveguiding channels. [13][14][15] The planar structures have demonstrated outstanding utility for applications demanding smaller form factors and reduced weights. Planar microwave structures, such as resonators and filters, have been investigated in passive and active configurations.…”
mentioning
confidence: 99%